Radiographers’ workload and burnout on performance: an empirical study - Arif, Wejdan M. (Frontiers in Public Health, 2024)
Study purpose To assess the prevalence of burnout among radiographers, and whether demographic variables and work-related factors had any influence on burnout and perceived stress among them. Methods A cross-sectional quantitative survey design is adopted in this study. The participants included radiographers from Saudi Arabia. Both Maslach Burnout Inventory (MBI) and Perceived Stress Scale (PSS) were used for data collection. Participation was voluntary, and the survey was conducted online, resulting in 322 final responses considered for the data analysis. Results The mean emotional exhaustion (EE) score achieved was 26.01, representing medium burnout risk. However, the mean depersonalization (DP: μ = 25.25) and personal accomplishment (PA: μ = 23.65) represented high burnout risk among radiographers. Statistically significant differences (p < 0.05) were observed among the participants grouped by genders, age groups, nature of work type, and work experience. The mean perceived stress score for radiographers was identified to be 27.8, indicating high. Conclusion The findings underscore the critical need for targeted interventions and support mechanisms within the radiology profession, particularly focusing on younger radiographers and those with extensive work experience.